2020
DOI: 10.3390/su12031174
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Cd2+ and Pb2+ on Aragonite Synthesized from Eggshell

Abstract: In the present work, waste eggshells were used as a precursor for the synthesis of aragonite crystals through the wet carbonation method. Cadmium (Cd2+) and lead (Pb2+) were removed by the synthesized aragonite from synthetic wastewater. The influence of initial solution pH, contact time, Cd2+ and Pb2+ concentration, and sorbent dosage were evaluated. The major sorption was observed in the first 100 mins and 360 mins for Pb2+and Cd2+ respectively reaching sorption equilibrium at 720 mins (12 hr). The sorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 46 publications
0
2
1
Order By: Relevance
“…The better fitness of the Freundlich model to the equilibrium data than that of the Langmuir model conforms to the results of Sukpreabprom et al 2014 who investigated the removal of Cd(II) using bottom ash. However, the findings of this study contradict other studies carried out to remove Cd(II) using cheap biosorbents in which the Langmuir model shows a dominant fit to the experimental data (Habte et al 2020;Kumar et al 2018;Kabir et al 2015).…”
Section: Freundlich Isotherm Modelcontrasting
confidence: 99%
“…The better fitness of the Freundlich model to the equilibrium data than that of the Langmuir model conforms to the results of Sukpreabprom et al 2014 who investigated the removal of Cd(II) using bottom ash. However, the findings of this study contradict other studies carried out to remove Cd(II) using cheap biosorbents in which the Langmuir model shows a dominant fit to the experimental data (Habte et al 2020;Kumar et al 2018;Kabir et al 2015).…”
Section: Freundlich Isotherm Modelcontrasting
confidence: 99%
“…Several researchers have studied the removal of heavy metals with natural limestone [ 13 , 14 , 15 ]. In recent years, various biogenic calcium carbonate wastes have been used as low-cost adsorbents to remove heavy metals from solutions such as eggshells [ 16 , 17 , 18 ], oyster shells [ 19 , 20 , 21 , 22 ], crustacean shells [ 23 ], clam shells [ 24 ], Anadara inaequivalvis shells [ 25 ], golden apple snail shells [ 26 ] and cockle shells [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sorption of Pb on the CaCO 3 surfaces is reported to be very high by Godelitsas et al [63] and they also reported that the mechanism of Pb sorption on the calcite surface also showed the formation of PbCO 3 (cerussite), formation of cerussite is helpful in reducing hazardous effects of Pb. Mechanism of sorption of heavy metals on the CaCO 3 precipitates is proposed to be ion exchange, precipitation of heavy metal carbonates and hydroxycarbonate forms, adsorption and complexation [64].…”
Section: Sorption Of Individual Heavy Metalsmentioning
confidence: 99%